2004
DOI: 10.2334/josnusd.46.37
|View full text |Cite
|
Sign up to set email alerts
|

The effect of basic fibroblast growth factor on cell cycle in human gingival fibroblasts from nifedipine responder and non-responder

Abstract: It has previously been demonstrated that gingival fibroblasts derived from nifedipine-reactive patients (nifedipine responders) show a greater cell proliferation rate than those from nifedipine non-reactive patients (nifedipine non-responders) in the presence of 1 microM nifedipine. The aim of the present study was to characterize cell cycle differences between nifedipine responder and non-responder fibroblast cells and determine the effect of basic fibroblast growth factor (bFGF) on cell cycle progression. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…In this study, we examined the effect of bFGF on cell cycle in NIFr and NIFn cells by flow cytometric DNA analysis after bromodeoxyuridine (BrdU, is incorporated into newly synthesized DNA by cells entering and progressing through the S phase of the cell cycle) incorporation. The present result, demonstrating that the proportion of NIFr cells that had undergone the G 1 / S transition in the presence of bFGF significantly increased compared to that in NIFn cells agreed with our previous results (22).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In this study, we examined the effect of bFGF on cell cycle in NIFr and NIFn cells by flow cytometric DNA analysis after bromodeoxyuridine (BrdU, is incorporated into newly synthesized DNA by cells entering and progressing through the S phase of the cell cycle) incorporation. The present result, demonstrating that the proportion of NIFr cells that had undergone the G 1 / S transition in the presence of bFGF significantly increased compared to that in NIFn cells agreed with our previous results (22).…”
Section: Discussionsupporting
confidence: 82%
“…This figure is a representative data out of four trials. previous study, it was indicated that the proportion of NIFr cells that had undergone progression to the S and G 2 / M phases from the G 0 / G 1 phase in the presence of bFGF was greater than that of NIFn cells (22). However, in the previous study, the S phase cells were not measured precisely, being calculated between the G 0 / G 1 and G 2 / M peaks in the DNA histogram.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations